Prawo do miasta — społeczna konstrukcja idei miejskości w przestrzeni Internetu - Rożałowska, Barbara (Studia Etnologiczne i Antropologiczne, 2015)
The study regards major social associations and individual initiatives in social networks, which carry out the idea of the right to the city. The object of analysis is the multimedia material posted on the Internet, capturing an image of a virtual city created by spontaneous actions of residents. The described visible activity is an expression of an arising reflective approach toward urban space. The change in residents’ mindsets about their role is facilitated by the network connection of participants. The efficacy of these networks creates an influential environment which has a considerable impact on today’s city management.